Structure of Crystallizable Polymer Solutions - Klenin, Vitaly J.; Fedusenko, Irina V. (Journal of Research Updates in Polymer Science, 2014)
Visually transparent solutions of crystallizable polymers in wide concentration and temperature ranges contain supramolecular particles which are fragments of the most perfect crystallites of condensed polymer. Though the fraction of these particles is usually with in 0.001-0.1wt % of the total polymer, their presence in a solution of macromolecules severely affects its physicochemical and technological properties (performance) and complicates (or even does not allow) the application of structurally-sensitive research techniques (e.g. lights cattering, dynamic birefringence, etc.). The parameters of the first-level supramolecular particles (just after visual dissolution) depend on the conditions of dissolution, storage, and the preliminary treatment temperature of the polymer. In wide polymer concentration and temperature ranges, a second level of the supramolecular particles ensemble is formed, with characteristic features of crystallization. From the formation rate of the second-level supramolecular particles, a microliquidus curve for them can be plotted. The paper presents data for the poly (vinyl alcohol) + water system which lack the area of liquid-liquid phase separation. Supramolecular particles parameters (average sizes, numerical and mass-volume concentration) were determined by means of the turbidity spectrum method.